Penggunaan Media Audio Visual dalam Meningkatkan Pemahaman Seni Tari pada Peserta Didik Kelas V SDN Ende 5 Kabupaten Ende - Antonia Y.W Wea; Maria Purnama Nduru; Frumensius B. Dole (Program Studi PGSD Universitas Flores, 2020)
The purpose of this research is to define the use of audio-visual media in improving dance understanding in students, to find out the understanding of dance after using audio-visual media. This type of research is a classroom action research (CAR). This research was conducted in a recurring cycle through four stages namely planning, implementing, observing, reflecting. This research was conducted at Ende 5 Elementary School in Ende Regency. The subjects in this study were grade V students, amounting to 28 people. The collection methods used are interviews, observation, documenta tion, and test. Analysis of the data used in this study is a qualitative descriptive analysis of teacher observation, observation of student learning activities and student understanding of the results. Based on the results of the evaluation of the first cycle with a percentage of mastery comprehension of students 50% with an average of 72.53%, the results of the evaluation of the second cycle with the percentage of completeness of students' understanding 82.14% with an average of 78.67% then the use of audio visual media can improve understanding dance with an increase of 6.14%.